ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN SUKARELA DALAM LAPORAN TAHUNAN PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Pratama, Atma; Anugerah, Rita; Anisma, Yuneita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The aims of this study is to analyze the influence of firm characteristics on voluntary disclosure in annual report in Indonesia. Factors tested in this study are ownership dispersion, firm age, leverage, return on equity. Collecting data is using porposive sampling methode to the manufacturing companies that listed in Indonesian Stock Exchange during 2012. This study uses content analysis to measure the extent of voluntary disclosure. There are 103 voluntary disclosure items to detect the extent of voluntary disclosure. This study used agency theory, stakeholder theory, and signal theory to explain lingkage between variables. This research uses multiple regression that use to examine the influence of firm characteristics on voluntary disclosure in annual report. The result of this research showed those independent variables that have significant influence on extent of voluntary disclosure is leverage and return on equity. However, firm age and ownership dispersion do not show significant influence on the extent of voluntary disclosures.Keywords: Annual Report, Firm Characteristics, Voluntary Disclosure, Voluntary Disclosure Items.